2021
DOI: 10.3390/ani11020504
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Glutamic Acid Modulates Immune Responses and Gut Health of Weaned Pigs

Abstract: Dietary glutamic acid (GLU) is used as a feed additive because of its functional characteristics that may affect the growth performance and health of pigs. This study was carried out to determine the effects of dietary GLU on growth performance, nutrient digestibility, immune responses, and intestinal health of weaned pigs. A total of ninety-six weaned pigs (8.07 ± 1.17 kg of body weight; 28 days of age) were assigned to two dietary treatments (8 pigs/pen; 6 replicates/treatment) in a randomized complete block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Stained sections were examined using a charge-coupled device camera-equipped microscope (TE2000; Nikon, Tokyo, Japan) with digital imaging software for measurements and counts (NIS Elements BR; Nikon Instruments Italia). The 15 longest and straightest villi and their associated crypts were selected to evaluate morphological changes [22]. The morphometric measurements of intestinal tissue were carried out as follows: villus height; crypt depth; villus height to crypt depth ratio (VH:CD); and the number of goblet cells.…”
Section: Sample Measurements and Analysismentioning
confidence: 99%
“…Stained sections were examined using a charge-coupled device camera-equipped microscope (TE2000; Nikon, Tokyo, Japan) with digital imaging software for measurements and counts (NIS Elements BR; Nikon Instruments Italia). The 15 longest and straightest villi and their associated crypts were selected to evaluate morphological changes [22]. The morphometric measurements of intestinal tissue were carried out as follows: villus height; crypt depth; villus height to crypt depth ratio (VH:CD); and the number of goblet cells.…”
Section: Sample Measurements and Analysismentioning
confidence: 99%
“…The gastrointestinal (GI) tract digests and absorbs nutrients while also acting as a barrier against harmful substances and pathogens ingested through the diet [ 1 ]. Pigs are exposed to a variety of pathogenic challenges, which causes the GI immune system to become activated [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Hu et al (2017), it was reported that supplementation of 1% Glu and 1.44% L‐alanine reduced BW and ADFI in growing‐finishing pigs. However, improvement in performance and nutrient digestibility were observed in weaned piglets fed 1% glutamine or 0.5% Glu supplemented diet (Kyoung et al, 2021; Zou et al, 2006). In the present study, the non‐significant effects on growth performance and nutrient digestibility in growing pigs receiving low CP diets may be due to the reduction of CP by only 2%.…”
Section: Discussionmentioning
confidence: 99%